Digital Transformation of Halal Supply Chain: A Global Bibliometric Analysis - Runtiningsih, Sri; Syarifah, Lailatis; Jayanto, Prabowo Yudo; Fauzi, Ahmad Syahrul; Mustofa, Ubaedul; Alirastra, Risanda (Likuid Jurnal Ekonomi Industri Halal, 2026)
The aim of this study is to explore the global development and digital transformation of halal supply chain research through a bibliometric analysis approach. Using 547 articles indexed in Scopus and published between 2008 and mid-2025, the study uses VOS viewer software to examine publication trends, co-authorship networks and thematic structures. The results indicate increasing scholarly interest, with dominant contributions from Southeast Asian countries. Key research clusters focus on halal logistics, traceability, blockchain, sustainability and the integration of digital technologies. The findings reveal a research gap in the empirical application of digital solutions. This study contributes to addressing this gap by mapping the current research landscape and recommending future empirical exploration to operationalise digital halal innovations.